Analysis Of Factors Affecting Rates Visit Atpublic Fuel Stations (Gas Station) (Case Study on SPBU 14201123) - Wulandari, Retno (Journal of Community Research and Service, 2024)
This research aims to determine the factors that influence the level of visits to SPBU 12201123 Jln. Gatot Subroto Medan. The object of this research was 100 visitors to SPBU 12201123 Jl. Gatot Subroto Medan. The research period is September to October 2023. The dependent variable in this study is the level of visits to gas stations 14201123 (Variable Y). The independent variables are the existence of an ATM (X1), the existence of a cafe (X2), the existence of a minimarket (X3) and the existence of a doormeer (X4). This research uses a multiple linear regression model which is calculated with the help of a programSPSS 25. Based on the results of multiple linear regression data processing, the results of the regression equation are Y = 2.952 – 0.233X1 – 0.194X2 + 0.218X3 + 0.414X4, which means that the existence of ATMs and Cafés does not have a significant effect on the level of visits to gas stations 12201123, while the existence of Minimarkets and Doorsmeer does. on the level of visits to gas stations 12201123. R test results2 shows that the 4 variables only have an influence of 4.3%, while the rest is generated by the influence of other variables outside this research.